Poles Apart - Painter, J (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2011)
Poles Apart is a wide-ranging comparative study on the prevalence of climate scepticism – in its various forms – in the media around the world. It focuses on newspapers in Brazil, China, France, India, the UK, and the USA, but includes an overview of research on the media of other countries. A wealth of new data is drawn from around 3,000 recent articles on climate change from two newspapers in each of the six countries. It concludes that climate scepticism is largely an Anglo-Saxon phenomenon, found most frequently in the US and British newspapers, and explores the reasons why this is so. The study also examines whether climate sceptics are more likely to appear in right-leaning than left-leaning newspapers, and in which parts of a newspaper their voices are most heard. Poles Apart includes a detailed survey of several hundred articles in ten British national newspapers to see where climate scepticism is most to be found, and which individual sceptics and organisations are most quoted.